STUDENTS CONCEPTIONS OF THE ENERGY CRISIS: A CROSS-SECTIONAL STUDY - Melati, Putri Sekar; Rustama, Nuryani; Rusyati, Lilit (Jurnal Visipena, 2025)
This cross-sectional study looks at how junior high and elementary school students think about crisis energy. The tool is sent out through an open-ended online survey. There were 167 people who took part in the study. The number of sixth-grade elementary school students (14), seventh-grade students (51), eighth-grade students (6), and ninth-grade students (96) in Bandung City. The study's results showed that ninth-grade students came up with the most ideas, followed by eighth- and seventh-grade students. The ninth graders came up with the idea that "environmental crisis" was the most crucial concept; among eight pupils, "energy limitation" seemed to be the most critical concept; and among high school students, “energy" was the most crucial concept. These results suggest that higher levels of education can help people come up with bigger ideas about crisis energy. This is because they can learn through theory or practice. Ninth graders now know more about ideas related to the energy crisis. The research has implications for teachers because it lets them teach students more advanced ideas about crisis energy in addition to the basics